Konfrontasi Kerajaan Allah dan Kuasa Iblis dalam Injil Sinoptik: The Confrontation Between the Kingdom of God and the Power of the Devil in the Synoptic Gospels - Sabriel Milleanno Lappu; Wilson Wiwi Suwanto (Journal of Religious and Socio-Cultural, 2023)
The Synoptic Gospels state that the presence of Christ marks the coming of the kingdom of God in the world (Mt 4:17, Mk 1:15, Lk 11:20). The coming of the kingdom of God is to defeat the kingdom and dominion of Satan, which the Bible also describes as the ruler of this world (Jn 12:31, 14:30, 16:11; Eph 6:12). Thus, there is a confrontation called warfare because the two parties are essentially different and cannot negotiate a middle ground: peace. This article aims to find the meaning of the confrontation of the kingdom of God against the power and kingdom of Satan in the Synoptic Gospels. In this article, the authors will specifically bring up fragments of confrontation or resistance carried out by the Kingdom of God in fighting the kingdom of Satan based on the Synoptic Gospels. The result of this study is that the Synoptic Gospels describing the story of Jesus’ death provide evidence that indicates the victory of the Kingdom of God against Satan’s power. Injil Sinoptik menyatakan bahwa kehadiran Kristus menandai datangnya kerajaan Allah di dalam dunia (Mat. 4:17, Mrk. 1:15, Luk. 11:20). Kedatangan Kerajaan Allah tersebut adalah untuk mengalahkan kerajaan dan kekuasaan Iblis yang Alkitab juga deskripsikan sebagai penguasa dunia ini (Yoh. 12:31, 14:30, 16:11; Ef. 6:12). Dengan demikian, terjadilah konfrontasi yang disebut peperangan, karena kedua pihak secara esensi memang berbeda dan tidak dapat berunding untuk memperoleh jalan tengah: perdamaian. Artikel ini bertujuan untuk menemukan makna konfrontasi kerajaan Allah terhadap kuasa dan kerajaan Iblis dalam Injil Sinoptik. Dalam artikel ini, para penulis secara khusus akan memunculkan fragmen-fragmen konfrontasi atau perlawanan yang dilakukan oleh Kerajaan Allah dalam memerangi kerajaan Iblis berdasarkan Injil Sinoptik. Hasil dari penelitian ini adalah Injil Sinoptik menggambarkan kisah kematian Yesus memberikan keterangan-keterangan yang mengindikasikan kemenangan konfrontasi Kerajaan Allah terhadap kuasa (kerajaan) Iblis.